Developing a pressure ulcer risk factor minimum data set and risk assessment framework. (21st May 2014) - Coleman, Susanne; Nelson, E. Andrea; Keen, Justin; Wilson, Lyn; McGinnis, Elizabeth; Dealey, Carol; Stubbs, Nikki; Muir, Delia; Farrin, Amanda; Dowding, Dawn; Schols, Jos M.G.A.; Cuddigan, Janet; et al.
Abstract Aim To agree a draft pressure ulcer risk factor Minimum Data Set to underpin the development of a new evidenced‐based Risk Assessment Framework. Background A recent systematic review identified the need for a pressure ulcer risk factor Minimum Data Set and development and validation of an evidenced‐based pressure ulcer Risk Assessment Framework. This was undertaken through the Pressure UlceR Programme Of reSEarch (RP‐PG‐0407‐10056), funded by the National Institute for Health Research and incorporates five phases. This article reports phase two, a consensus study. Design Consensus study. Method A modified nominal group technique based on the Research and Development/University of California at Los Angeles appropriateness method. This incorporated an expert group, review of the evidence and the views of a Patient and Public Involvement service user group. Data were collected December 2010–December 2011. Findings The risk factors and assessment items of the Minimum Data Set (including immobility, pressure ulcer and skin status, perfusion, diabetes, skin moisture, sensory perception and nutrition) were agreed. In addition, a draft Risk Assessment Framework incorporating all Minimum Data Set items was developed, comprising a two stage assessment process (screening and detailed full assessment) and decision pathways. Conclusion The draft Risk Assessment Framework will undergo further design and pre‐testing with clinical nurses to assess and improve its usability. It will then be evaluated in clinical practice to assess its validity and reliability. The Minimum Data Set could be used in future for large scale risk factor studies informing refinement of the Risk Assessment Framework.